Research on influencing factors of production control valve used for water control in horizontal wells. (6th September 2021) - Feng, Zhang; Hanxiang, Wang; Ming, Wang
In this paper, in view of the heterogeneity caused by the physical properties of a reservoir and lithologic differences in horizontal wells, which can easily become locally watered out in horizontal section, the production control valve which can adjust the flow rate is used to control the production of horizontal wells in sections, which is an effective method to delay edge and bottom water inrush. The results show that the smaller the opening of control valves is, the stronger the balance degree of liquid production profile is, and the balance degree of liquid production profile gradually decreases with the increase of the number of control valves. When installing the control valve, its parameters should be optimised. Through the simulation of the production flow pressure chart, the optimal production is selected, and the corresponding bottom hole flow pressure and optimal production pressure difference are selected.